Economies of private sector participation in solid waste management in Takoradi - a Ghanaian city (Journal of Science and Technology, 2016)
Without going into the complex intricacies of the controversial privatisation debate that have since the 1980s ensued, this paper evaluates the economic feasibility of private sector participation in solid waste management in a Ghanaian city context. The criteria for identifying viable economic opportunities for investment are contingent to the prevailing market conditions. The primary consideration, inevitably, is the potential profit that can be derived. On the supply side, the weight of the premium placed on borrowed capital is a fundamental determining factor. On the demand side, the business prospects of private sector participation in solid waste management depends on the nature and the scale of cost recovery consequent upon the payment regime negotiated and accepted by the residents. It has been established through a case study of Takoradi that private sector participation in solid waste management in the city is a viable business venture within certain contextual conditions. An important consideration is the ability and willingness to pay by the residents. The designated payment regime is such that the returns are adequate to finance the service provision and leave a modest outlay to the investor as profit. On the part of the investor, the ease of access to investment capital and a congenial macro-economic environment are important determinants of successful business.